2016
DOI: 10.1186/s12936-016-1623-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and determinants of malaria risk in urban and peri-urban areas of Blantyre, Malawi

Abstract: BackgroundAlthough malaria disease in urban and peri-urban areas of sub-Saharan Africa is a growing concern, the epidemiologic patterns and drivers of transmission in these settings remain poorly understood. Factors associated with variation in malaria risk in urban and peri-urban areas were evaluated in this study.MethodsA health facility-based, age and location-matched, case–control study of children 6–59 months of age was conducted in four urban and two peri-urban health facilities (HF) of Blantyre city, Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 28 publications
7
65
3
Order By: Relevance
“…Transmission levels recorded during this study in the city of Yaoundé were far above these values as well as those previously recorded [23,60]. Additionally, such high levels likely point to the negative influence of unplanned urbanisation on malaria transmission and are consistent with studies conducted in other major sub-Saharan African cities [6,30,34,37,42,43,48,50,54,69].…”
Section: Discussionsupporting
confidence: 90%
“…Transmission levels recorded during this study in the city of Yaoundé were far above these values as well as those previously recorded [23,60]. Additionally, such high levels likely point to the negative influence of unplanned urbanisation on malaria transmission and are consistent with studies conducted in other major sub-Saharan African cities [6,30,34,37,42,43,48,50,54,69].…”
Section: Discussionsupporting
confidence: 90%
“…Other risk factors for malaria revealed in the study include lower education level, not sleeping under bed nets and not using Indoor Residual Spraying (IRS). Mathanga et al [ 14 ] compared malaria risk factors in urban and peri-urban areas in Malawi. Univariate analysis indicated that lower risk was associated with possession of a TV, electricity in the household and having a higher education.…”
Section: Introductionmentioning
confidence: 99%
“…Univariate analysis indicated that lower risk was associated with possession of a TV, electricity in the household and having a higher education. People living in urban and peri-urban areas had the same risk factors associated with contracting malaria [ 14 ]. Zgambo et al [ 15 ] compared malaria risk factors identified in the 2012 and 2014 Malaria Indicator Survey (MIS) and found that older children and those living in poor households were associated with contracting malaria in both 2012 and 2014 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Possible justi cations for the higher occurrence of malaria among males and older age group could be their engagement in various outdoor activities and staying outdoors during the nights [38]. Apart from outdoor exposures, differences in treatment-seeking behavior, access to health facilities and travel history [39] might be the possible contributors for the sex-and age-based variations of malaria cases. In addition, a review report revealed that adult females are better protected from parasitic diseases than males due to genetic and biological (hormonal) factors [40].…”
Section: Discussionmentioning
confidence: 99%
“…This could be because of massive construction activities (like road, house and small dams) and presence of coffee processing sites in Dilla town and its vicinity that could create suitable habitat for mosquito breeding. Travel history [39], differences in the competence and skills of the laboratory personnel and relatively good reporting system might also be the main responsible factors in uencing the prevalence of malaria in Dilla town compared to rural districts. There have been healthy ongoing malaria control activities incorporating environmental management, indoor residual spraying (IRS), long-lasting insecticide-treated nets (LLINs) and artemisinin-based combination therapy in the area.…”
Section: Discussionmentioning
confidence: 99%